The role of pectic enzymes on cloud stability of kalamansi juice (Citrus Microcarpa Bunge) - Radomvivat, Pairin; Alabastro, Estrella F. (1986)
The physico-chemical properties of fresh kalamansi juice were studied. The presence of the enzyme pectinesterase (PE) was also established/ Its activity, measure in terms of methanol release, was found to be 8.94 ug/ml juice. Polygalacturonase was absent. Fractions of pectic substances found were: high methoxy pectin of water-soluble fraction (WSF), 0.0535 mg/gm AIS; low-methoxy pectin or exalate-soluble fraction (OSF), 0.278 gm/gm AIS; and protopectin or acid-soluble fraction (ASF), 0.0540 gm/gm AIS. The effect of heat treatments of 1 min at 80°C and 1 min at 90°C on the cloud stability of the juice during storage at room temperature for 12 days was also studied. The pH values of the untreated (Control) and heat-treated samples decreased slightly during storage. Percent soluble solids in all samples did not change with storage Turbidity values of the unheated juice decreased abruptly from zero day to the second day, followed by a gradual decrease thereafter. In contrast, heat-treated samples at both temperatures exhibited a gradual decrease in turbidity all throught the storage period. Viscosity changes followed the same trend. The WSF and OSF of untreated samples were lower while ASF was higher as compared to the corresponding values of both heat-treated samples at the start of the storage period. Statistical analysis showed that there were significant differences between untreated and heat-treated samples all throughout the storage period for all pectin fractions (WSF, OSF, ASF) but there was no significant difference between the two heat treatments. Methanol release in the unheated sample increased abruptly from 8.94 ug/mg juice to 23.11 ug/ml juice from zero to 2nd day of storage after which time the increase in methanol was more gradual. In the heat treated samples there was very little change in the amount of methanol.
Thesis (M.S.)--University of the Philippines, Diliman.
Typescript.
Keywords: Pectin; Pectinase; Kalamansi juice -- Storage